Strengthening transboundary groundwater management in the Shire Aquifer System of Malawi and Mozambique through the Groundwater for aDvancing Resilience (G4DR) in Africa project - Zuma, Cebolenkosi; Kumwenda, Steven (International Water Management Institute, 2025)
The Shire Aquifer System, shared by Malawi and Mozambique, is a lifeline for communities that rely on it for drinking water, irrigation, and the maintenance of healthy ecosystems. However, pressures from over-abstraction, pollution, limited governance, and climate change threaten its sustainability. Through the Groundwater for aDvancing Resilience (G4DR) in Africa project, IWMI and the ministries of Water in Malawi and Mozambique, along with other stakeholders in the landscape, are working to enhance groundwater management in the basin. Efforts focus on developing a joint monitoring network, improving data sharing, strengthening institutional arrangements, and building capacity.